At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

solve the equation 2x(2-6)=4(3+1x-2)​

Sagot :

Answer:

no solution

Step-by-step explanation:

if you distribute and simplify:

4x-12 = 12+4x-8

4x-12 = 4x+4

-12 ≠ 4

Answer:

[tex]x = - \frac{1}{3} [/tex]

Step-by-step explanation:

1) Simplify 2 - 6 to -4.

[tex]2x \times - 4 = 4(3 + 1 \times x - 2)[/tex]

2) Simplify 1 × x to x.

[tex]2x \times - 4 = 4(3 + x - 2)[/tex]

3) Simplify 3 + x - 2 to x + 1.

[tex]2x \times - 4 = 4(x + 1)[/tex]

4) Simplify 2x × -4 to -8x.

[tex] - 8x = 4(x + 1)[/tex]

5) Divide both sides by 4.

[tex] - 2x = x + 1[/tex]

6) Subtract x from both sides.

[tex] - 2x - x = 1[/tex]

7) Simplify -2x - x to -3x.

[tex] - 3x = 1[/tex]

8) Divide both sides by -3.

[tex]x = - \frac{1}{3} [/tex]

Therefor, the answer is x = -1/3.